Ameloblastin Peptides Modulates the Osteogenic Capacity of Human Mesenchymal Stem Cells - Stakkestad, Øystein; Lyngstadaas, Ståle P.; Vondrasek, Jiri; Gordeladze, Jan O.; Reseland, Janne Elin (Frontiers in Physiology, 2017)
During amelogenesis the extracellular enamel matrix protein AMBN is quickly processed into 17 kDa (N-terminus) and 23 kDa (C-terminus) fragments. In particular, alternatively spliced regions derived by exon 5 / 6 within the N-terminus region are known to be critical in biomineralization. Human mesenchymal stem cells (hMSC) also express and secrete AMBN, but it is unclear if this expression has effects on the hMSC themselves. If, as suggested from previous findings, AMBN act as a signaling molecule, such effects could influence hMSC growth and differentiation, as well as promoting the secretion of other signaling proteins like cytokines and chemokines. If AMBN is found to modulate stem cell behavior and fate, it will impact our understanding on how extracellular matrix molecules can have multiple roles during development ontogenesis, mineralization and healing of mesenchymal tissues. Here we show that synthetic peptides representing exon 5 promote hMSC proliferation. Interestingly, this effect is inhibited by the application of a 15 aa peptide representing the alternatively spliced start of exon 6. Both peptides also influence gene expression of RUNX2 and osteocalcin, and promote calcium deposition in cultures, indicating a positive influence on the osteogenic capacity of hMSC. We also show that the full-length AMBN-WT and N-terminus region enhance the secretion of RANTES, IP-10, and IL-8. In contrast, the AMBN C-terminus fragment and the exon 5 deleted AMBN (DelEx5) have no detectable effects on any of the parameters investigated. These findings suggest the signaling effect of AMBN is conveyed by processed products, whereas the effect on proliferation is differentially modulated through alternative splicing during gene expression.